2023
DOI: 10.1021/jacs.2c11295
|View full text |Cite
|
Sign up to set email alerts
|

EnT-Mediated N–S Bond Homolysis of a Bifunctional Reagent Leading to Aliphatic Sulfonyl Fluorides

Abstract: Sulfur(VI) fluoride exchange (SuFEx) gives rise to a plethora of high-valent sulfur linkages; however, the availability of (aliphatic) sulfonyl fluoride manifolds lag behind, owing to the limited sources of introducing the SO2F moiety via a classical two-electron approach. Recently, radical-based methodologies have emerged as a complementary strategy to increase the diversity of accessible click partners. In this work, synthesis of a bench-stable sulfamoyl fluoride reagent is presented, which may undergo sigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 92 publications
1
36
0
Order By: Relevance
“…On the basis of these observations and previous reports, a possible mechanism is proposed (Scheme d). Initially, the photosensitizer absorbed the light to form the triplet exited benzophone * .…”
supporting
confidence: 64%
“…On the basis of these observations and previous reports, a possible mechanism is proposed (Scheme d). Initially, the photosensitizer absorbed the light to form the triplet exited benzophone * .…”
supporting
confidence: 64%
“…For example, Luo and Willis recently demonstrated that N -sulfonyl imines could be utilized as a sulfonyl radical source in the monofunctionalization of alkenes through energy transfer catalysis. To our knowledge, the utilization of sulfonamides as bifunctional reagents in organic synthesis remains rare (Figure b) …”
mentioning
confidence: 99%
“…Recently, Glorious and co-workers developed a novel method to synthesize β-amino sulfonyl fluorides through addition of both amine and SO 2 F groups into alkenes using (diphenylmethylene)sulfamoyl fluoride as a novel reagent for imino-fluorosulfonylation ( Scheme 26 ). 86 Reactions were carried out in a single step by treatment of alkenes with (diphenylmethylene)sulfamoyl fluoride in the presence of thioxanthone as a photocatalyst in DMC under blue LED irradiation at room temperature for 24 hours. Styrenes containing various functional groups were tolerated with this process to give the corresponding di-substitutes product 93a in good yield.…”
Section: S–x Bond Formation Reactionmentioning
confidence: 99%